Economic socialization program for the enterprise business interdependencies of rural tourism-experiential in Caraz, Ancash - Paredes Tarazona, Mildred (2012)
Quasi-experimental study design, evaluation before and after intentional sample of volunteers from urban neighborhoods Associates Huaylas APEMYPE Caraz and rural Asociacion SHOCSHAVivencial to answer: How it affects the economic socialization program interdependencies to entrepreneurship in tourism business rural-experiential in Caraz, Ancash. DATA collected by Attitude Scale - ESCAIETA - 2011) of 0.86 for reliability and Knowledge Survey No.1 Alternative Tourism (E1CTA-2011): Rural-to Experiential Training Program. Was processed and analyzed the data by statisticians not parametric, dependent variable (DV) Attitudes towards enterprise interdependencies for alternative tourism venture, Rural / Experiential, Independent Variable effect of (VI) Workshops: Economic Terms partnerships Strategy business and institutional management and the control variable (CV) Status of experiential tourism activities focused on the rescue of cultural products (UNESCO 2005). Previous diagnosis of probable entrepreneurs by neighborhood groups and information of the project, agreed to two intervention groups. Observed confusion on the modalities of Tourism before the application of ESCAIETA-2011 (before and after application of the VI, 9 workshops). Attitudes towards business Interdependence for entrepreneurship are positive, with an increasing trend, short make a significant difference or a very positive move, being expressed that their activities in the tourism sector not for profit REDITA opposite is more share the adventure. Null hypothesis is accepted, the Program of economic socialization in business and institutional interdependencies to guide the rural-tourism venture in experiential Caraz, Ancash not affected.